Creatine kinase and endocrine responses of elite players pre, during, and post rugby league match play - McLellan, C. P.; Lovell, D. I.; Gass, G. C. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to (a) examine player-movement patterns to determine total distance covered during competitive Rugby League match play using global positioning systems (GPSs) and (b) examine pre, during, and postmatch creatine kinase (CK) and endocrine responses to competitive Rugby League match play. Seventeen elite rugby league players were monitored for a single game. Player movement patterns were recorded using portable GPS units (SPI-Pro, GPSports, Canberra, Australia). Saliva and blood samples were collected 24 hours prematch, 30 minutes prematch, 30 minutes postmatch, and then at 24-hour intervals for a period of 5 days postmatch to determine plasma CK and salivary testosterone, cortisol, and testosterone:cortisol ratio (T:C). The change in the dependent variables at each sample collection time was compared to 24-hour prematch measures. Backs and forwards traveled distances 5,747 ± 1,095 and 4,774 ± 1,186 m, respectively, throughout the match. Cortisol and CK increased significantly (p < 0.05) from 30 minutes prematch to 30 minutes postmatch. Creatine kinase increased significantly (p < 0.05) postmatch, with peak CK concentration measured 24 hours postmatch (889.25 ± 238.27 U/L). Cortisol displayed a clear pattern of response with significant (p < 0.05) elevations up to 24 hours postmatch, compared with 24 hours prematch. The GPS was able to successfully provide data on player-movement patterns during competitive rugby league match play. The CK and endocrine profile identified acute muscle damage and a catabolic state associated with Rugby League match play. A return to normal T:C within 48 hours postmatch indicates that a minimum period of 48 hours is required for endocrine homeostasis postcompetition. Creatine kinase remained elevated despite 120 hours of recovery postmatch identifying that a prolonged period of at least 5 days modified activity is required to achieve full recovery after muscle damage during competitive Rugby League match play.